Food and beverage purchasing procedures of de-luxe class hotels in Metro-Manila, Philippines - An, Kwang-Ho; Gatchalian, Corazon F. (1988)
This is a descriptive study on the food and beverage purchasing procedures of 12 deluxe class hotels in Metro-Manila licensed by the Department of Tourism. Utilizing the questionnaire as a tool with purchasing managers as respondents, information were obtained on: general characteristics of the hotels, selected aspects of the food and beverage outlets, the organizational set-up of the purchasing departments, the personal qualifications of the purchasing managers, the purchasing procedures based on food and beverage specifications, selection of suppliers, methods and buying frequency, receiving procedures, and manner of payment. The level of satisfaction of purchasing managers over existing purchasing procedures was likewise measured. General Characteristics of the Hotel Most deluxe class hotels were established in 1976. Eleven hotels were owned by corporations and ten of them were shared with foreigners. Only one was owned solely by Filipinos. The number of rooms in all hotels studied ranged from a minimum of 272 to a maximum of 676. Rates per day ranged from USD 52-150 for deluxe, USD 160-180 for executive; and USD 165-2000 for the suite. The deluxe type was the most common type of room available for sale. Foreign tourists were the most frequent guests. Hotel income was derived largely from room sales, followed by beverage sales and others. February, August and January were reported as the peak months while October, March, September, May and December were reported as the lean months. Personal Qualifications of the Purchasing Manager All purchasing managers in the hotels studied were Filipinos. Among them, six were male and five were female. Six of eleven managers were within the age range of 31 to 35, four were 36 to 40 years old, and only one belonged to the 41 to 45 age range. Seven purchasing managers finished college and four had graduate degrees in different areas of study. All purchasing managers had previous work experience in the hotel industry. Nine had 10-15 years experience, while one had 15-20, and another one had more than 20 years of experience. Four purchasing managers have been in their position for eight years, and therefore, served the longest in their present position. The shortest length of service rendered by a respondents as purchasing manager was less than a year, backed up by 15 years of hotel experience in a different position. Purchasing Procedures Lack of knowledge in market conditions was the most common problem identified in preparing the food and beverage specifications. Reasonable price offering and technical ability of the supplier were considered as the most important factors in selecting suppliers. Late deliveries and non-compliance with quality were the most common problems encountered in purchasing food and beverage items. Majority of the hotels did not have a formal or an official tool for evaluation of suppliers. Quality and price were the most important factors considered essential in purchasing. Competitive or open market, contract and negotiated buying methods were most commonly employed in the hotels. Although seven purchasing managers were satisfied and four were very satisfied with the overall existing purchasing procedures in their respective hotels, the findings in this study pointed out that there is a need for setting up of a rotation for the purchasing managers' position, to set-up a formal or an official evaluation tool for the suppliers' performance, the need for improvement in the preparation, the specifications, selection of suppliers and the enhancement of relationships between the purchaser and supplier.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Hotels -- Philippines -- Metropolitan Manila Area -- Purchasing; Beverages -- Purchasing; Marketing (Home economics).